THE PYGMALION EFFECT IN TEACHING ACTIVITIES AND ADMNISTRATIVE - Gutiérrez Huby, Ana María (2010)
The intention of this article takes of showing confidence and success expectations even from a student in their academic work and achievements to a worker in their administrative functional activities and productivity, deepening in the positive consequences obtained when the “Pygmalion effect” is applied in the classroom and in the offices of the educational institution, as the negative consequences that causes to ignore or underestimate their respective capacities.